ANALISIS DAMPAK ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN TERHADAP KESEJAHTERAAN PETANI PEMILIK LAHAN DI KELURAHAN TUREN KECAMATAN TUREN KABUPATEN MALANG - Zaky, Achmad; Maryunani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine what factors encourage land-owning farming communities to carry out land conversion and to determine the impact of land-use conversion by land-owning farmers in Turen Village, Turen District, Malang Regency. The method used is descriptive quantitative. The results of this study indicate that the conversion of agricultural land to non-agricultural land that occurred in Turen Village, Malang Regency District, occurred due to 3 main factors, namely internal factors, external factors, and economic factors. These three factors are the main reasons for respondents to carry out land conversion. The conversion of the land function itself has an unfavorable impact on the level of welfare, especially at the income level of land-owning farmers in Turen Village. Because in total there were only 3 respondents or 20.0% of respondents who experienced an increase in income after carrying out land conversion.